Risks and Safety of Advanced Therapies and Biologics in Inflammatory Bowel Disease: A Review for Nurses. (July 2020) - Morvillo, Cynthia; Vinci, Katherine; Hedenschoug, Lauren; Mancini, Leah; Mize, Carrie; Tugg, Kayce; Stein, Steven
Abstract : Advanced therapies, including biologics, are a core component of managing inflammatory bowel disease, which is increasing in prevalence. These therapies may offer an improved safety and tolerability profile compared with conventional treatments. However, they can interact with a patient's immune system via different mechanisms. Healthcare providers need to be aware of the possible adverse effects, such as infection and immune-mediated reactions, as well as risk management methods, such as patient screening and vaccination. As central members of the multidisciplinary team, nurses have an important role in educating patients with inflammatory bowel disease on disease course, treatment options, monitoring patient adherence, and response to treatment. This narrative review summarizes key safety considerations for the treatment of inflammatory bowel disease with advanced therapies, including risk of infection and malignancy; immunologic, metabolic, and hematologic complications; and what nurses can do to manage these risks. Special considerations for pediatric, elderly, and pregnant populations are also discussed.